Malignant hypertension secondary to renin-producing hepatoblastoma - Doinita Sfrijan; Cristian Scurtu; Mihaela Paca; Dan-Alexandru Iozsa (Indian Journal of Medical and Paediatric Oncology)
Clinical presentation of hepatoblastoma is often insidious and its paraneoplastic manifestations are not uncommon. We report an extremely rare case of a renin-secreting hepatoblastoma inducing malignant hypertension remarked in our clinic. The hepatic malignancy classified as PRETEXT IV and a multidisciplinary approach according to SIOPEL III was made with a poor outcome. Hepatoblastoma in children should be considered as possible etiology of hypertension in children.